Noninvasive Imaging of Acute Renal Allograft Rejection by Ultrasound Detection of Microbubbles Targeted to T-lymphocytes in Rats - Grabner, A.; Kentrup, D.; Mühlmeister, M.; Pawelski, H.; Biermann, C.; Bettinger, T.; Pavenstädt, H.; Schlatter, E.; Tiemann, K.; Reuter, S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: We propose CD3-antibody-mediated contrast-enhanced ultrasonography using human T-lymphocytes for image-based diagnosis of acute allograft rejection (AR) established in a rat renal transplantation model.Materials and Methods: 15 minutes after tail vein injection of 30 × 106 human T-lymphocytes, contrast media/microbubbles conjugated with an anti-human CD3 antibody was applied to uni-nephrectomized 10-week-old allogeneically transplanted male rats (Lewis-Brown Norway (LBN) to Lewis, aTX) and ultrasound was performed to investigate the transplanted kidney as well as the native kidney. In vivo results were confirmed via immunohistochemical stainings of CD3 after post mortem dissection. Syngeneically transplanted rats (LBN to LBN, sTX), rats with ischemia/reperfusion injury (IRI, 45 min. warm ischemia), and rats subjected to acute cyclosporin A toxicity (CSA) (cyclosporine 50 mg/kg BW for 2 days i. p.) served as controls.Results: Accumulation of human T-lymphocytes was clearly detected by antibody-mediated sonography und was significantly increased in allografts undergoing AR (5.41 ± 1.32 A. U.) when compared to native control kidneys (0.70 ± 0.08 A. U.). CD3 signal intensity was low in native kidneys, sTX (0.99 ± 0.30 A. U.), CSA (0.10 ± 0.02 A. U.) and kidneys with IRI (0.46 ± 0.29 A. U.). Quantification of the ultrasound signal correlated significantly with the T-cell numbers obtained by immunohistochemical analysis (R2 = 0.57).Conclusion: Contrast-enhanced sonography using CD3-antibodies is an option for quick and highly specific assessment of AR in a rat model of renal transplantation.
Keywords: diagnostic radiology; ultrasound; molecular imaging; microbubbles; transplantation